Flood Disaster Mitigation as Revealed by Cawang-Manggarai River Improvement of Ciliwung River - Airlangga Mardjono (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2013)
Ciliwung River that flows from Bogor highland is one of the rivers traversing several lowlands in Jakarta. Having the lowland topographic condition, the area along Ciliwung River is potentially inundated. Flood disaster that occurred in early 2002 in Jakarta caused a wide inundation area (with approximately 25% area of Jakarta Province being flooded), serious damages in properties, and also loss of life.This paper presents hydraulic routing analysis over Ciliwung River within the Cawang - Manggarai reach through several scenarios and further simulation using of HEC RAS 3.1 version Software. From the several scenarios and simulations, a conclusion among scenarios which results the lowest water surface elevation was withdrawn.The final result of this simulation shows that Scenario 3 gives the lowest water surface elevation profile. Scenario 3 is subjected to river normalization, revetment works along the river, and also flood control structure improvement through the additional sluice gate on Manggarai Barrage. This scenario results 167 cm, 163 cm, 172 cm, 179 cm, 167 cm and 171 cm or 17,60%, 17,16%, 18,09%, 18,76%, 17,38% and 17,72% of maximum water level reduction respectively over cross section number S 20 to S 25, for several simulations with 100 year of design discharge.Keywords: Simulation, river improvement, flood water surface elevation.